Efektivitas Prebiotik Berbasis Kacang-Kacangan Dalam Pakan Buatan Terhadap Laju Pertumbuhan Ikan Bandeng - Wahyudi, Wahyudi; Aslamyah, Siti; Surianti, Surianti (Universitas Mataram, 2025)
The purpose of this study was to evaluate the effectiveness of legume-based prebiotics in milkfish feed, with the hope of increasing growth rate, survival rate, and feed efficiency. The study was conducted using five feed treatments containing soybean flour, peanuts, green beans, red beans, and control. Feed was given at a percentage of 5% of fish biomass per day for 60 days. The results showed that feed containing red beans (Feed D) gave the best results, with a survival rate of 77.777% and the highest specific growth rate of 12.937%. However, the feed conversion ratio was not significant. Feeding containing red beans is thought to improve the performance of fish digestive microflora, contribute to improved health and feed digestibility, and support faster growth. However, although increased survival and growth were achieved, feed utilization efficiency (FCR) still needs to be improved. This study shows that red bean-based feed has the potential to increase milkfish cultivation results sustainably, but feed management and environmental factors are also very important to support cultivation efficiency.